Evaluation of vaccine rooms: a Brazilian case study (Research, Society and Development, 2022)
The study aims to evaluate the situation of vaccine rooms in a Brazilian city based on the standard required by the Ministry of Health, in Primary Health Care. This is an evaluative research, with a qualitative approach, carried out in Campina Grande-PB. Interviews were carried out with 15 nurses, technicians responsible for the vaccine rooms, with a script based on the Instrument for Supervision of Vaccination Rooms of the National Immunization Program, considered the gold standard in the evaluation of this service. Data were submitted to Content Analysis. The standard was not reached in several items evaluated, with the local reality permeated by particular situations that interfere with the quality of services: lack of immunobiological and vaccinators, culminating in vaccine delay; professionals' lack of knowledge about the reasons for vaccine contraindications and about the notification of vaccine-prevented diseases in the coverage area; lack of standard operating procedure for carrying out the activities inherent to the vaccination process. The vaccine rooms in the studied municipality are in disagreement with ministerial norms, which makes it difficult to implement good vaccine practices, in this context, the fragility of the municipality's responsibility regarding the planning and organization of vaccine rooms is perceived. Thus, there is a need for investment to improve the physical structure of the rooms and equipment; to promote the training and continuing education of professionals to work in the vaccine room.